DETERMINING HEALTH PROFESSIONALS' KNOWLEDGE LEVELS ON CHILD ABUSE AND NEGLECT. - TUĞUT, Nilüfer; DAŞLI, Yılmaz (Electronic Turkish Studies, 2019)
The present study was conducted to determine health professionals' (physicians, nurses, midwives) knowledge levels of the signs and risk factors of child abuse and neglect. The study is a descriptive study. The study was conducted at Family Health Centers in Sivas. There are 26 Family Health Centers in the city center. Because it was targeted to include all the population, the sample size was not calculated (N:178). The study data were collected with the Personal Information Form and The Diagnose the Signs and Risks of Child Abuse and Neglect Scale. The data were analyzed using the IBM SPSS (Statistical Package for Social Sciences) 21.0 program. Nearly half of the nurses and more than half of the midwives and physicians were trained on child abuse and neglect. However, almost all of them stated that they were competent enough to recognize the signs of child neglect and abuse but that they needed more information about this issue anyway. Regarding the recognition of the signs of child abuse and neglect, nurses obtained higher knowledge scores than did the physicians, and the physicians obtained higher scores than did the midwives but the differences were insignificant. In terms of identifying the characteristics of children vulnerable to abuse and neglect, the physicians were better than nurses, and nurses were better than midwives. It was determined that very few of the nurses and about one-fourth of the midwives and physicians encountered abuse and neglect cases. While more than half of the nurses and physicians reported the abuse and neglect cases they encountered to the police, more than half of the midwives only informed the parents. The only difference between those who received training on this issue and those who did not during their education was the way the they recognized the signs of neglect in children. While the health professionals obtained the highest scores from the recognizing the characteristics of children vulnerable to abuse and neglect subscale, they obtained the lowest scores for recognizing the characteristics of parents tending to perpetrate abuse and neglect. It was determined that the health professionals' knowledge of some aspects of abuse was not sufficient.